Polyethylene microplastics affect the distribution of gut microbiota and inflammation development in mice - Li, Boqing; Ding, Yunfei; Cheng, Xue; Sheng, Dandan; Xu, Zheng; Rong, Qianyu; Wu, Yulong; Zhao, Huilin; Ji, Xiaofei; Zhang, Ying (Chemosphere (Oxford), 2020)
Environmental pollution caused by plastics has become a public health problem. However, the effect of microplastics on gut microbiota, inflammation development and their underlying mechanisms are not well characterized. In the present study, we assessed the effect of exposure to different amounts of polyethylene microplastics (6, 60, and 600 μg/day for 5 consecutive weeks) in a C57BL/6 mice model. Treatment with a high concentration of microplastics increased the numbers of gut microbial species, bacterial abundance, and flora diversity. Feeding groups showed a significant increase in Staphylococcus abundance alongside a significant decrease in Parabacteroides abundance, as compared to the blank (untreated) group. In addition, serum levels of interleukin-1α in all feeding groups were significantly greater than that in the blank group. Of note, treatment with microplastics decreased the percentage of Th17 and Treg cells among CD4+ cells, while no significant difference was observed between the blank and treatment groups with respect to the Th17/Treg cell ratio. The intestine (colon and duodenum) of mice fed high-concentration microplastics showed obvious inflammation and higher TLR4, AP-1, and IRF5 expression. Thus, polyethylene microplastics can induce intestinal dysbacteriosis and inflammation, which provides a theoretical basis for the prevention and treatment of microplastics-related diseases. •Polyethylene microplastics affected the composition and diversity of gut microbiota.•Polyethylene microplastics increased the secretion of IL-1α in serum.•Polyethylene microplastics decreased the Th17 and Treg cells among CD4+ cells.•High-concentration polyethylene microplastics induced small intestinal inflammation.